Bioremediation of shrimp (Litopenaeus vannamei) cultured effluent using copepod (Oithona rigida) and microalgae (Picochlorum maculatam & Amphora sp.)—An integrated approach. Issue 54 (19th November 2016) - Dinesh Kumar, S.; Santhanam, P.; Nandakumar, R.; Ananth, S.; Nithya, P.; Dhanalakshmi, B.; Kim, Mi-Kyung
Abstract: Nitrogenous compounds are major contaminants in aquaculture effluent and thereby needs a potential candidate for removing these nutrients. The present study tested the efficacy of immobilized microalga, diatom Amphora sp. and copepod Oithona rigida to remove excessive nutrients from the shrimp ( Litopenaeus vannamei ) cultured effluents. Nutrient removal was evaluated with five different combinations: (1) copepod, O. rigida ; (2) immobilized Picochlorum maculatum and copepod O. rigida ; (3) immobilized P. maculatum ; (4) immobilized Amphora sp. and copepod O. rigida ; and only (5) immobilized diatom, Amphora sp. Preliminary studies showed maximum reduction of about nitrate 86% and nitrite 88% in treatment 2–4, respectively. The maximum phosphate (69%) and ammonia (91%) removal was recorded in the treatment 3. In disparity, the phosphate concentration recorded was significantly higher (6%) at the end of the experiment in the treatment 1 than other experiments. While in the treatments 1, 2, and 4 the copepod showed significant (ANOVA: p < 0.001) increases in phosphate from the previous concentration, it might be due to the rapid release of this nutrient from excreta of filter-feeding organism. The results showed that immobilized green alga and copepod performed well in absorbing phosphate, ammonia, and nitrogenous compounds, respectively.